СОВРЕМЕННЫЕ ИННОВАЦИОННЫЕ ПОДХОДЫ К РАЗВИТИЮ ГОСТИНИЧНОГО БИЗНЕСА В МИРЕ И ПРАКТИКЕ КАЗАХСТАНА (International Journal of Innovative Technologies in Economy, 2019)
The article provides an analysis of the development of hotel in Kazakhstan for 2015-2018. The study is based on statistical information about results of the work hotels according to data from Statistics Committee Ministry of National Economy Republic of Kazakhstan. Moreover, in this article is studied modern innovative approaches to development of hotel in the world, to assess their implementation into practice Kazakh hotels. The results of research confirm the improvement of developing of hotel in Kazakhstan for 2015-2018 and slow implementation innovative approaches to development of Kazakh hotels.